Analisis Prinsip Ownership Hak Cipta Terhadap Karya Hasil Artificial Intelligence (AI) Dalam Perspektif Hukum Positif - Mukhasibi, Muhammad Akmal; Widodo, Selamat (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
The rapid development of Artificial Intelligence (AI) has created new challenges for copyright law, especially in terms of ownership, originality, and creativity. This study focuses on two main issues: how Indonesian copyright law regulates the ownership of works created by AI, and the legal impact on the principles of originality and creativity. The method used is normative juridical, based on library research, and refers to Law Number 28 of 2014 on Copyright and other related regulations. The results show that only humans can be legal subjects who own copyright under Indonesian law. AI is considered only a tool, not a creator. However, there is still no clear legal standard to measure how much human involvement is needed in an AI-generated work for it to be considered original. This causes legal uncertainty in determining the rightful owner and the protection of AI-based works. Therefore, the law must adapt by providing clear guidelines to ensure copyright protection remains relevant in the digital era. The state needs to respond normatively and quickly to provide legal certainty and protect the economic rights of creators in facing AI development.